التكوين النفسي للحكمة الفارسية في الشعر العربي بين البُستيّ والطغرائيّ: The Psychological Formation of Persian Wisdom in Arabic Poetry between Al-Busti and Al-Tughra'i - Baraa Khaled Hilal,; Dr. Abdulmujeeb Bassam, (Al Manhal Research Journal, 2024)
The relationship between Persian and Arabic governance after Islam constituted an important part of the development of Islamic civilization, leading to the exchange of culture and knowledge among the peoples in the region. However, in this brief study, we will not delve into the indirect influences between the two cultures. Instead, we will focus on two Persian poets who lived and died in Persia, both of whom adopted Arabic language and culture as the language of science and civilization in which they wrote their poetry. Specifically, we will examine the most famous poems of each, "Lamiyyat al-Ajam" by al-Tughra'i, the vizier, and the poem by Abu al-Fath al-Busti. We will compare two poets from the same culture and environment, with a slight difference in the era they lived in. Their poems were rich with inherited wisdom from the traditions of Persia and the Sassanid dynasty, but the motivations and directions of that wisdom differed with each poet's personality. This study employs an analytical balance to answer the most important question about the difference between Busti's and Tughra'i's wisdom, driven by the psychological makeup of each poet.